Emerging Self‐Powered Autonomous Sensing Triboelectric Fibers toward Future Wearable Human‐Computer Interaction Devices. Issue 2 (15th January 2023) - Ning, Chuan; Zheng, Guoqiang; Dong, Kai
Abstract: Wearable electronic technology is developing rapidly and has been widely used in human‐computer interaction, smart homes, telemedicine, rehabilitation training, sports monitoring, object tracking, etc. Fibers, as the basic elements of clothing, have become important carriers of wearable electronics. The fiber‐shaped triboelectric nanogenerator (F‐TENG) is typically a 1D structure that is highly flexible and can be woven from 1D to 2D or even 3D textiles. F‐TENG has both the structural characteristics of fibers and the function of energy conversion of the triboelectric nanogenerator (TENG). Therefore, it can be worn on the body both as an energy converter to convert the mechanical energy of human movement into electrical energy and as a self‐powered sensor to convert human movement information into electrical signals. Herein, this review comprehensively introduces the recent progress of F‐TENG, including the scale preparation method of fibers, the weaving method of fibers, triboelectric‐based multifunctional fiber, and various fibers for energy harvesting and self‐powered sensing. Finally, the challenges and opportunities in the field of F‐TENG are discussed. Abstract : The review comprehensively introduces the recent progress of fiber‐shaped triboelectric nanogenerator (F‐TENG) including methods for the scale preparation of F‐TENG, the weaving methods (2D and 3D) for F‐TENGs, F‐TENGs for self‐powered sensing and multifunctional textiles for energy harvesting and storage. In addition, several challenges and opportunities for F‐TENG in practical applications are summarized.